Effectiveness of Container Cargo Information Management System at Ports: Role of Competency Training, Shore-Based Personnel, and Technology at Indonesian Container Terminals - Ferro Hidayah; Natanael Suranta; Yusuf Pria Utama (International Journal of Mechanical, Industrial and Control Systems Engineering, 2026)
This research investigates the effectiveness of container cargo information management systems at Indonesian ports, examining the critical roles of competency training, shore-based personnel capabilities, and technology adoption in determining system performance and operational outcomes. Container terminals increasingly rely on sophisticated information systems including Terminal Operating Systems (TOS), Port Community Systems (PCS), and Electronic Data Interchange (EDI) for coordinating complex cargo operations, yet system effectiveness depends not solely on technology sophistication but critically on personnel competency, training adequacy, and human-technology integration. Through qualitative analysis involving terminal operators, port information system managers, shore-based operational personnel, training coordinators, and technology providers, this study examines how the interplay between human capabilities and technological capabilities determines information system effectiveness. Results demonstrate that comprehensive competency training programs can improve system utilization effectiveness by 45-65%, reduce operational errors by 50-70%, and enhance productivity by 25-40% through better human-technology integration. Key challenges include inadequate training investment, high personnel turnover, technology complexity exceeding user capabilities, and organizational resistance to systematic training programs. Findings reveal that container terminal information system effectiveness depends fundamentally on sociotechnical system optimization addressing both technological infrastructure and human capability development through sustained competency building programs. This research contributes to port operations literature by providing evidence-based frameworks for human factors integration in port technology implementation.